2012
DOI: 10.1016/j.nlm.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Opioid mechanisms are involved in the disruption of arcaine-induced amnesia by context pre-exposure

Abstract: Previous exposure to the training context disrupts glutamatergic N-methyl-d-aspartate receptor (NMDAr) antagonist-induced amnesia, indicating that novelty is necessary for such an amnestic effect. While there are reports that novelty-related release of opioids cause amnesia, no study has addressed whether the amnestic effect of NMDAr antagonists involve opioid mechanisms. In this study we investigated whether pharmacological manipulation of the opioid system immediately after context pre-exposure alters the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Arcaine (a potent antagonist for the PA binding site on the NMDAr) at 0.002–0.2 nmol had either no effect or prevented Spd-associated consolidation during stepdown and inhibitory avoidance tasks. Spd (0.02–2 nmol) generally improved fear conditioning acquisition and consolidation whereas arcaine (0.0002–0.02 nmol or 10–30 mg/kg) treatment impaired this acquisition (Rubin et al, 2004 ; Camera et al, 2007 ; Da Rosa et al, 2012 ; Signor et al, 2014 ; Guerra and Rubin, 2016 and references therein). PAs also modify reconsolidation and extinction of fear conditioning and step-down avoidance, but the observed effects evaluated by different investigators were variable.…”
Section: Pas and Human Healthmentioning
confidence: 99%
“…Arcaine (a potent antagonist for the PA binding site on the NMDAr) at 0.002–0.2 nmol had either no effect or prevented Spd-associated consolidation during stepdown and inhibitory avoidance tasks. Spd (0.02–2 nmol) generally improved fear conditioning acquisition and consolidation whereas arcaine (0.0002–0.02 nmol or 10–30 mg/kg) treatment impaired this acquisition (Rubin et al, 2004 ; Camera et al, 2007 ; Da Rosa et al, 2012 ; Signor et al, 2014 ; Guerra and Rubin, 2016 and references therein). PAs also modify reconsolidation and extinction of fear conditioning and step-down avoidance, but the observed effects evaluated by different investigators were variable.…”
Section: Pas and Human Healthmentioning
confidence: 99%
“…Numerous reports have indicated that polyamines improve memory in several tasks and attenuate memory deficits induced by different amnesic agents [ 32 - 41 ]. In fact, agonists and antagonists of the polyamine binding site at the NMDA receptor respectively facilitate and impair memory in various tasks [ 33 , 34 , 36 , 39 , 40 , 42 , 43 ], and the sequential activation of protein kinase C (PKC) and PKA/CREB (protein kinase A/cAMP response element-binding protein) pathways in the hippocampus has been implicated in the promnesic effect of polyamines [ 44 , 45 ]. However, it has recently been described that interruption of the NMDA receptor modulation by polyamines reverses Aβ 25–35 -induced memory impairment in mice in a novel object recognition task [ 46 ], suggesting that the role of polyamines in memory may vary in physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%